The sensitivity of calorie-income demand elasticity to price changes: evidence from Indonesia - Skoufias, Emmanuel (International Food Policy Research Institute, 2002)
The calorie-income demand elasticity is an important parameter in the development literature and in the policy arena. Yet, there is very little evidence on the extent to which it can be considered as an unchanging parameter or a time-shifting parameter that, for example, changes with the economic conditions faced by households. In this paper I use data from the 1996 and 1999 National Socio-Economic Surveys (SUSENAS) in Indonesia to examine whether the relationship between income changes and caloric availability has changed and if so, how. Using the same questionnaire, the SUSENAS surveys collect detailed information on more than 200 different food items consumed over the last seven days by 60,000 households at the same point in each survey year. I use nonparametric as well as regression methods to examine two important relationships: (1) between income and total calories, and (2) between income and calories from cereals and other foods (excluding cereals and root crops). The empirical analysis finds that the income elasticity of the demand for total calories is slightly higher in February 1999 (the crisis year with dramatically different relative prices) compared to its level in February 1996. Also, the calorie-income elasticity for cereals as a group increases while the calorie-income elasticity for other food items decreases. The latter finding is interpreted as consistent with the presence of a binding subsistence constraint.